The Effectiveness of Using Kahoot in Teaching Arabic at Junior High School - Ahmad Fajar; Julianti Julianti (Kalimatuna: Journal of Arabic Research, 2023)
In Arabic, there are four maharah that must be mastered, namely maharah istima', kalam, qiroah and kitabah. To master these four skills, effective learning media is needed and in accordance with the times. Unfortunately, many teachers are less creative in using existing media. Learning media has a role as an attractor of attention, curiosity and facilitates the delivery of information to students. This paper discusses Kahoot learning media in the Arabic learning process at Ibnu Sina Al-Qanun Junior High School, Purwakarta. Kahoot is a learning medium in the form of a web-based application for creating quizzes and simple games. Teachers as content creators can add elements in the form of videos, images and text and students can access them via Android. This research is a type of descriptive qualitative research with primary data sources in the form of interviews and questionnaires to students and related parties as well as secondary observation data. Data collection techniques use documentary methods. Meanwhile, data analysis uses qualitative analysis. The results showed that Kahoot learning media can improve students' Arabic language skills at Ibnu Sina Al-Qanun Junior High School, Purwakarta. The purpose of this study is to make teachers more creative in utilizing learning media to create an efficient and more enjoyable learning process.